Habilidades pragmáticas em crianças com transtorno do espectro autista em telefonoaudiologia durante a pandemia Covid-19. - Lima, Rauanne Thais Barbosa Ferreira de (2023)
The year 2020 started with many challenges. In March, emergency measures were installed due to the COVID-19 pandemic decreed by the World Health Organization (WHO) and, with that, the whole world had to adapt to the new reality, such as the case of children with Autistic Spectrum Disorder (ASD). The Federal Council of Speech Therapy has issued notes and guidelines for conducting telephonoaudiology. In view of this, the scenario of social isolation, caused by the pandemic, promoted changes in routine activities that started to be adapted to the remote format (online). In this sense, the overall objective of this dissertation was to investigate the pragmatic language skills of children diagnosed with Autism Spectrum Disorder in therapeutic interaction online, following the specific objectives: analyze the pragmatic resources used in the statements of autistic subjects in digital context; describe the pragmatic functioning of language in a framework of functional communication between autistic child and his interlocutor through digital platform, as well as identify in the pragmatic language area unique enunciative modes of language functioning in autistic subjects. For this, we opted, as a method, for qualitative research of the case study type in a descriptive way, relating enunciative scenes of autism and telecare in speech therapy. We used as theoretical foundation the works of Barros (2006, 2011, 2016), Benveniste (2020), Kanner (1945), Farrell (2008), Flores (2010), Fernandes (1996), Barros and Fonte (2016, 2020), among others. The conclusion demonstrated that the use of telephonoaudiology in the period of the COVID-19 pandemic did not interfere with the dynamics and advances of clinical speech therapy care. Interaction between subjects, intention and communicative knowledge of the children participating in the study were perceived, as well as the presence of several pragmatic skills found in enunciative scenes of remote therapy. This fact allows us to think of other therapeutic strategies for language construction using the digital medium as a vehicle for the promotion and signification of enunciates, as long as the interlocutor accepts the autistic child as a subject of possibilities, allowing a place in language.